An outbreak of RSV infections in a neonatology clinic during the RSV-season - Liliya Vakrilova; Stanislava Hitrova Nikolova; Sergei Slavov; Petya Radulova; Boryana Slancheva (BMC, 2021)
Abstract Background Respiratory syncytial virus (RSV) is the predominant cause of lower respiratory tract infections (LRTI) in infancy. Preterm infants with bronchopulmonary dysplasia (BPD) are at the highest risk of severe RSV-LRTI. This is a retrospective study that analyses a nosocomial outbreak of RSV infections in the Neonatology clinic of the University Hospital of Obstetrics and Gynecology, Sofia, 2019. Methods Two groups of infants without contact between them were diagnosed with RSV-infection: 14 infants were treated in the Department for healthy newborns - Group 1, and 7 preterm infants were treated in the Neonatal Intensive Care Unit (NICU) - Group 2. The detection of RSV was performed using Real-Time PCR in nasal/throat swabs. Results Respiratory symptoms occurred 2-5 days after discharge in 14 of 148 healthy term infants born February 5 to 18, 2019; 12 babies were re-hospitalized with LRTI and recovered in a few days. RSV-PCR was positive in 6 infants, while in the others, RSV etiology was suggested, due to similar symptoms and contact between them. The first NICU patient with RSV-LRTI was one of the 26 gestational weeks (GW) twins, who had severe BPD. The other twin was always discharged home without LRTI-symptoms. In the period February 19 to March 15, 2019, 26 premature babies born at 26-34 GW, were tested for RSV (33 nasal/throat swabs). They received a first or subsequent palivizumab injection. We identified 11 positive samples in 7 of the babies. Despite the clinical recovery, the second RSV-PCR remained positive in 4 babies. Six of the 7 NICU patients had symptoms of LRTI, and two of them needed mechanical ventilation. Six babies were discharged home after stabilization, one was transferred to the Pediatric department for further treatment of BPD and later discharged too. Conclusions This was the most serious outbreak of RSV infections in neonates since the RSV-PCR diagnostic in Bulgaria was introduced. The course of RSV-LRTI was severe in extremely preterm patients with underlying BPD. So, routine in-hospital RSV-prophylaxis with palivizumab should be considered for infants at the highest risk.